Issue Cost and Method of IPO Underwriting: Japan's Change from Auction Method Pricing to Book Building - Kenji Kutsuna; Richard L. Smith (Claremont McKenna College, Department of Economics, 2000)
In 1997, Japan introduced book building an alternative to an auction method of IPO pricing that had been required since 1989. Shortly after its authorization, all IPOs in Japan were priced by book building. The shift occurred despite economic arguments and evidence suggesting that the auction method reduced underpricing. We attribute the shift to creation of an information-based pooling equilibrium where low quality firms that benefit from the imposed auction regime lose the benefit if high quality firms are free to select book building. We examine the effects of the regime change on total issue cost and characteristics of IPO firms. We find that, on average, total issue cost during the auction period would have been similar under book building, but that the regimes have differential effects. For large well-established issuers, book building reduced total issue cost. Small issuers had lower cost under the auction method, but high-quality small firms appear to have been foreclosed from issuing. Ignoring the effect of pricing method on underinvestment, our estimates of the simple average cost advantage of the auction method range from 6.9 percent of aftermarket value to 1.8 percent. Because, from a cost standpoint, book building benefits large issuers, the value-weighted effect of the book building method is unambiguously positive, averaging 136 million Yen per issuer in our sample, or 3.5 percent of aftermarket value. In aggregate, we estimate that reliance on the auction method from 1995 through late 1997 cost JASDAQ issuers 61 billion Yen more than book building would have cost. This estimate does not include any additional costs associated with underinvestment.
Keywords: 330